Beautiful news - McCandless, David, ....- (Londen : William Collins, 2021)
In this fascinating follow-up to the bestselling Information is Beautiful and Knowledge is Beautiful, the king of infographics David McCandless uses spectacular visuals to give us all a bit of good news.
Autor of Information is Beautiful
Keywords: Datavisualisatie; Trends